2001
DOI: 10.1046/j.1365-2818.2001.00777.x
|View full text |Cite
|
Sign up to set email alerts
|

Orientation averaging of electron backscattered diffraction data

Abstract: SummaryThe use of data averaging to improve the angular precision of electron backscattered diffraction (EBSD) maps is discussed. It is shown that orientations may be conveniently and rapidly averaged using the four Euler-symmetric parameters which are coefficients of a quaternion representation. The processing of EBSD data requires the use of an edge preserving filter and a modified Kuwahara filter has been successfully implemented and tested. Three passes of such a filter have been shown to reduce orientatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
116
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(117 citation statements)
references
References 14 publications
1
116
0
Order By: Relevance
“…And finally, for ELEE, HMF, SNN, Kuwahara, and the adaptive Wiener filters, a window size of 5 × 5 pixels was used in the numerical evaluation of these filters. This choice of window size for these filters is also commonly made in the literature [24][25][26][27][28][29][30][31][32][33][34][35][41][42][43][44][45]. On the other hand, for an OCT image to be filtered, the optimum choice of this window size should also take into account the residual correlation between two adjacent pixels of the OCT image.…”
Section: Introductionmentioning
confidence: 99%
“…And finally, for ELEE, HMF, SNN, Kuwahara, and the adaptive Wiener filters, a window size of 5 × 5 pixels was used in the numerical evaluation of these filters. This choice of window size for these filters is also commonly made in the literature [24][25][26][27][28][29][30][31][32][33][34][35][41][42][43][44][45]. On the other hand, for an OCT image to be filtered, the optimum choice of this window size should also take into account the residual correlation between two adjacent pixels of the OCT image.…”
Section: Introductionmentioning
confidence: 99%
“…Defining q GB Ͻ0.5°would be desirable in order to be in accordance with the result from the point counting method. However, this value is within the angular resolution of EBSP indexing (normally ϳ1°in conventional mapping 17) ) and could result in abnormal behavior in the process. Therefore, the grain boundary definition angle was set to 1.5°, even though the resulting martensite volume fraction is underestimated frequently.…”
Section: Description Of the Methodsmentioning
confidence: 98%
“…An approach to solve this thresholding problem is to use an edge-preserving lowpass filter to smooth the data. Humphreys et al [47] have implemented a Kuwahara filter, which reduces the noise in a data set by statistically analysing neighbourhoods surrounding every point. Each pixel is iteratively replaced with the average of the neighbourhood with the least variance.…”
Section: An Automated Methods For Reconstructing Various Types Of Bounmentioning
confidence: 99%
“…The highlighted microbands in figure 11b are isolated in 3D in figure 11c to show the nature of the interior of the segmentation. This data set was also segmented with the Kuwahara filter method [47]. It was found that, while this type of filter partially aligns with the visible microband structure, no threshold value was found to be appropriate for the entire data set, which was evidenced by the presence of both significant oversegmentation and undersegmentation.…”
Section: Microbands In Cold Rolled Aluminiummentioning
confidence: 99%